Sistematización de experiencias en gestión documental y servicio al cliente interno y externo de la dirección de posgrado, Universidad Técnica de Cotopaxi, (UTC) - Calapiña Velva, Sandra Maribel (2019)
The present systematization work was carried out in the Postgraduate Management, Technical University of Cotopaxi, (TUC), with the collaboration of 329 involved, among internal and external clients and administrative staff of the dependency. The main objective of the systematization is to propose the increase of the alphanumeric and chronological file systems in a physical and digital way, since with the increase of these two systems it is intended to improve the organization in the entry and exit of the documents to the different dependencies that all the documents are used daily and there are possibilities that they are damaged or lost due to constant manipulations when not knowing exactly where the required documents are, causing loss of time and documental disorganization. In this way it is intended to develop efficient and effective performance in the activities, taking into account all the techniques and quality development that is used at the time of receiving, archiving and keeping any type of document that has been made and finally the training constant to the administrative staff regarding the updating of the archiving systems in document management and customer service whose purpose is to improve the quality and professionalism in the service and attention provided to customers and that through the survey carried out could see that the Postgraduate secretary is not updated with the methods in document management and customer service which has caused discomfort by not being able to resolve or provide the information requested; this increase would help to improve the organization and the correct order in the documents, the satisfaction and the interest of the clients, considering the need that the agency only uses the alphabetical file system